Public defenders versus private attorneys: A comparison of criminal case disposition outcomes by type of counsel in Mexico - Quintana-Navarrete, Miguel (Criminology & criminal justice, 2025)
Recent research on the effectiveness of public defenders vis-à-vis private attorneys in criminal cases has not exhaustively analyzed trial avoiding mechanisms and other pretrial outcomes and expanded beyond the United States. This article addresses these gaps using a novel data set from the Mexican criminal justice system, where trial avoiding mechanisms have been recently introduced. We show that both private and public defenders avoid trials, but at different costs. Cases with private attorneys are more likely to end in dismissals, especially via alternative procedures (dispute resolution mechanisms and diversion), while cases with public defenders are more likely to end in convictions through abbreviated procedures (guilty pleas). Resource constraints and their membership to the courtroom workgroup might incentivize or pressure public defenders to cooperate with the prosecution to secure a guilty plea, thus facilitating the conviction of defendants in administrative procedures that lack the full due process protections of trials.